Activation of macrophages by quinonyl-N-acetylmuramyl dipeptide. - Saiki, I (1983)
The effect of 6-O-QS-10-N-acetylmuramyl-L-valyl-D-isoglutamine methyl ester (quinonyl-MDP-66) on various functions of macrophages was examined. Mouse peritoneal macrophages, when treated either in vitro or in vivo with quinonyl-MDP-66 suspended in phosphate-buffered saline, showed a capacity for cytolysis and cytostasis against tumor targets and released H2O2 in the presence of phorbol myristate acetate. The macrophages induced by quinonyl-MDP-66 also had both antibody-dependent cell-mediated cytotoxicity and phagocytic activity against erythroid targets. The fact that synthetic quinonyl-MDP-66 stimulates the macrophages to become more cytotoxic than do other MDP analogs suggests that the lipophilic residue (QS-10) in quinonyl-MDP-66 may be important for the development of this activity.